The permanent vegetative state: clinical objectivity, ethical problems and answers of care. - Gigli, Gian Luigi (Medicina e Morale, 2002)
The author, to the light of the more up-to-date specialistic literature, illustrates the two clinical conditions defined as persistent vegetative state respectively permanent vegetative state. They are two conditions in turn to them distinguished by other clinical situations as coma and cerebral death. In fact, the persistent vegetative state (specifying that the vegetative state is the complete loss of conscience also in presence of sleeping-waking cycles and of hypotalamic and autonomic brain stem activity) is a condition present to distance of one month from a cerebral trauma or for at least one month in metabolic or degenerative pathologies or in malformative syndromes. Instead, the permanent vegetative state is an irreversible condition, according the definition of Multi-Society Task Force on Pvs, even if it is a prognostic index and not a diagnosis of certainty. Therefore, while the persistent vegetative state is a defined diagnosis, the permanent vagetative state represents a probability evalutation. In the second part of the article, the author illustrates the debate of clinical bioethics risen about this matter, warning from unacceptable attempts of surreptitious introduction of euthanasia for these patients.